Fault characteristics (System protection technology)
The objective of this module is to discuss the characteristics of different types of faults and their effects on the power system. Knowledge of this material is vital to understanding the protective schemes that are presented in the modules that follow. Topics include: effects of load impedance and short circuit impedance on current flow, grounding: safety grounding; neutral grounding; delta system grounding transformer; aerial ground wires on transmission lines, ungrounded systems-hazards & ground fault detection, phasor diagrams for different types of faults, production of positive, negative and zero sequence components, effect of negative and zero sequence components, rules for study of symmetrical components.